STRATEGI FRONT OFFICE DEPARTEMEN DI GRAND PURI SARON BOUTIQUE HOTEL YOGYAKARTA DALAM MENINGKATKAN KUALITAS PELAYANAN TAMU - Nawing, Aditya Yuwana; Telaumbanua, Selvi Yardina (JURNAL NUSANTARA, 2023)
This study aims to explore strategies conducted by front office department to improve its quality of guest services. The rapid growth of hotels in Yogyakarta has led to the emergence of fierce competition amongst hotel industry, therefore, it is crucial for hotels to determine strategies in order to improve their quality of service to hotel guests. Hotel service quality is essential, particularly in the formation of hotel image amongst guests, as this image could highly influences guest’s decission to make a repeat visit or to give recommendation to oend the hotel to others. Front office department, through the quality of service of its staff, has an important role in giving a good impression of a hotel. One indicator of its service quality assessments is the suitability of front office staff in conducting their duties with the standard operating procedures of this department . In the context of the Grand Puri Saron Boutique Hotel Yogyakarta, the standard operating procedures of the front office department are still not implemented properly; one of which is related to the delivery of important information to guests, causing guests to file complaints. Therefore, the researcher considers that research on the front office department strategies in improving the quality of guest services at Grand Puri Saron Boutique Hotel Yogyakarta is important to carry out. The results of this study are an explanation of the front office department's strategies in improving the quality of guest services according to the standard operating procedures in order to increase the occupancy rate of hotel rooms; this includes the way staff in this department handle guest complaints in accordance with standard operating procedures.